1999
DOI: 10.1046/j.1365-2044.1999.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected complication of the intubating laryngeal mask

Abstract: SummaryFatal oesophageal perforation occurred as a complication of elective general anaesthesia for cataract extraction in a 77-year-old female patient. Tracheal intubation had been achieved, albeit with difficulty, in the course of a clinical trial of the intubating laryngeal mask.Keywords Equipment; intubating laryngeal mask. Complications. ...................................................................................... Correspondence to: Dr M. A. Branthwaite Accepted: 30 May 1998 The laryngeal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 5 publications
(10 reference statements)
1
35
0
Order By: Relevance
“…A case of an esophageal perforation has also been reported after five blind intubation attempts were made through the FT-LMA. 82 Kihara et al 83 compared the FT-LMA with the C-LMA in ASA I and II female patients and found that use of the FT-LMA resulted in significantly more minor complications, such as sore mouth and difficulty swallowing. Minimizing excessive force during blind intubation may prevent injury to the larynx or avoid oropharyngeal pain after FT-LMA removal.…”
Section: Complications and Limitationsmentioning
confidence: 99%
“…A case of an esophageal perforation has also been reported after five blind intubation attempts were made through the FT-LMA. 82 Kihara et al 83 compared the FT-LMA with the C-LMA in ASA I and II female patients and found that use of the FT-LMA resulted in significantly more minor complications, such as sore mouth and difficulty swallowing. Minimizing excessive force during blind intubation may prevent injury to the larynx or avoid oropharyngeal pain after FT-LMA removal.…”
Section: Complications and Limitationsmentioning
confidence: 99%
“…Blind tracheal intubation (TI) attempts can result in esophageal intubation and/or airway trauma. 10,11 Although rare, major complications can occur. TT with tips that exert higher forces and pressures may be at higher risk for causing esophageal and/or airway damage during blind TI attempts via the ILMA.…”
mentioning
confidence: 99%
“…3 However, this blind technique might damage pathological changes near the laryngeal inlet, such as an esophageal pouch. 20 Therefore, caution is required in using the blind technique, 2 1 particularly when there is resistance during the advancement of a tracheal tube or when ventilation via the mask is suboptimal. We recommend the use of a fibrescope whenever it is available.…”
Section: Discussionmentioning
confidence: 99%